Workplace Romance: Examining Romance Motives and Organization Policies in Indonesia - Amanda, Hiroko Jodi Brigitte Laura; Mustika, Martina Dwi (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research aimed to predict a person’s intention to have a romantic relationship at work, seen from the motives (love and work) and types of policies (strict, warning, no policy) that existed in the company. Romance in the workplace was a common phenomenon in organizations, but this behavior was still considered sensitive to be investigated in Indonesia. In total, 268 Indonesian employees aged 20-40 years who worked at least six months in a company participated in the 2x3 factorial experimental vignette method, and for data analysis, it used repeated measured ANOVA. The research results have found that several types of company policies determine a person’s intention to have romance at work. The stricter the rules and the heavier the punishment, the less likely a person will engage in romance at work. However, on the motive, it is found that there is no difference between the types of motives and one’s intentions in a workplace romance. Finally, the interaction between motives and policies is not significant enough to predict a person’s intention to engage in romance at work. Therefore, it can be concluded that in Indonesia, the implementation of policies still has an essential role in reducing the negative impact of romance in the workplace. Other variables can still be included for future research to see the factors influencing a person’s intentions in workplace romance.